The concept of public control over judges’ activity and the system of subjects of its implementation - N. V. Nestor (Law and Safety)
The author of the article substantiates the modern tendency of the formation, development and spread of an increasing number of levers and protectors from state’s abuse of power, change of the state’s essence and its purpose in the society. The public and various elements of its control and supervisory activity play a significant role in this. Theoretical aspects of the issue of public control in general or in the context of a certain sphere of state power functioning, in particular are studied. Considering this, the author offers own definition of the category of public control over judges (courts) in Ukraine. The system and the legal status of various public control subjects are briefly characterized, their classification is performed and the place of control over judges among other subjects is determined.